EXPERIMENTAL CARDIOVASCULAR AND LUNG RESEARCHSevere multivessel coronary artery disease and high-sensitive troponin T - Huziuk, Inga Magdalena; Lelonek, Małgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : A key problem in stable coronary artery disease (CAD) is non-invasive identification of patients with severe multivessel CAD. Determination of biomarkers that have pro-inflammatory properties (C-reactive protein – hsCRP) and indicate heart muscle ischemia (high-sensitive troponin T – hsTnT) can contribute to the improvement of stratification in this regard. The aim of the study was to identify factors associated with the presence of multivessel CAD in clinically stable men. Material and methods: The study included 92 symptomatic men (mean age 64.05 ± 9.42 years) with preserved left ventricular function, scheduled for elective coronary angiography. Patients were divided and analyzed in two groups: with multivessel coronary artery disease (2-3-vessel disease, n = 46) vs. without multivessel coronary artery disease (n = 46). Results: Patients with multivessel CAD had significantly higher levels of hsTnT (0.01 vs. 0.007, p = 0.0021) and fasting glucose (6.0 vs. 5.45, p = 0.0112). Based on the drawn ROC curves, the cut-off points were determined for hsTnT ≥ 0.0085 ng/ml and fasting plasma glucose ≥ 5.85 mmol/l. From multivariate analysis only hsTnT in concentration higher than the cut-off point enhanced the risk of multivessel CAD (OR 4.286, 95% CI: 1.79-10.263, p = 0.001). Conclusions: In men with stable CAD, preserved systolic left ventricular function and non-high cardiovascular risk determined from the initial concentration of hsCRP, elevated level of hsTnT was independently associated with the risk of multivessel coronary artery disease.